Sustainability of castor based intercropping systems under varied planting geometry: Sustainability of castor based intercropping systems under varied planting geometry - KESHAVAMURTHY; J S YADAV (Journal of Oilseeds Research, 2020)
The field experiment was conducted with the objective to assess the performance of castor based intercropping system. The experiment was laid out in randomized block design and replicated thrice with 8 treatment combinations. The results indicated that 180 cm row spaced castor intercropped with methi resulted in higher seed yield. The 240 cm row spaced castor intercropped with methi resulted in higher gross return and net return whereas 240 cm row spaced castor intercropped with mung bean gave highest B: C ratio.